Kindergarten management system - Chuah, Ee Sing (2025)
The Kindergarten Management System (KMS) project aims to improve administrative efficiency in kindergartens by addressing the limitations of manual record-keeping, ineffective communication, and lack of digital payment options. Most kindergartens still use old-fashioned methods, which often lead to delays, mistakes, and things running less smoothly day to day. This project seeks to enhance an existing KMS by incorporating better communication tools, stronger security measures, and online payment integration. The new system will add messaging, email alerts, and virtual meetings to make it easier for teachers, parents, and school staff to stay connected and communicate smoothly. Multimedia support for announcements and Q&A sections will provide clearer and more engaging communication. To ensure data security, the project will implement Multi-Factor Authentication (MFA), password encryption, CAPTCHA verification, and automated backups, protecting sensitive school information from unauthorized access. A safe online payment system makes collecting fees easier and faster, so there's less manual work and payments come in on time. This project builds upon existing KMS platforms by addressing their weaknesses and incorporating advanced features. The result will be a more efficient, secure, and user-friendly system that improves communication, strengthens security, and simplifies administrative tasks in kindergartens.